ASSESSING THE IMPACT OF FINANCIAL ACCOUNTING DATA ON MANAGERIAL DECISION-MAKING IN EGYPT’S MEDIUM AND SMALL-SIZED ORGANIZATION - Mgadami, Shafik Yousef Ahmed; Musa, Ali Albasheer Himah (The journal of contemporary issues in business and government, 2022)
The goal of this study is to learn more about the financial practises used by Small and Medium Sized Enterprises (SMEs) in Egypt, especially those that are located in emerging markets. Reports on accounting procedures are essential for tracking all accounting functions. Accounting data, such as the cash flow and income statements assertion reports seen in corporate financial records, is used by management to make decisions. The current study looks at how financial accounting reporting affects small and medium-sized businesses in Egypt. The incremental innovation, the focus strategy, and the cluster method are only a few of the strategies that have been developed to encourage the growth of the entrepreneurial sector in Egypt, based on the economic pathway change. The study also looks into the administration's perspective on capital distribution to see if it maximises the decision's efficacy. Cross-sectional data strategy was applied for this aim, and 200 managers and employees of SMEs who responded to a standardised questionnaire provided the data. The primary goal of this study is to examine the difficulties faced by Egyptian entrepreneurship as they launch their Small and Medium Enterprises (SMEs). The study found that a favourable link between financial accounting reports and managerial actions is mediated by the ability, relevancy, and quality of accounting statements.